2017
DOI: 10.1242/jeb.156661
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary solution of terrestrial isopods to cope with low atmospheric oxygen levels

Abstract: The evolution of current terrestrial life was founded by major waves of land invasion coinciding with high atmospheric oxygen content. These waves were followed by periods with substantially reduced oxygen concentration and accompanied by the evolution of novel traits. Reproduction and development are limiting factors for evolutionary water-land transitions, and brood care has probably facilitated land invasion. Peracarid crustaceans provide parental care for their offspring by brooding the early stages within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…At the same time, the gas exchange area remains relatively constant and the egg membrane acts as a diffusion barrier which can lead to a mismatch between oxygen supply and demand. The consequences of such oxygen limitation are hatching delays (Fernández et al 2003 ) and subsequent catch-up growth even when favourable conditions for larval life are reinstated (Petersen and Anger 1997 ; Warkentin 2002 ; Horváthová et al 2017 ). Several studies have shown changes in mass exponents through the ontogeny of different taxa which is in agreement with our findings (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the gas exchange area remains relatively constant and the egg membrane acts as a diffusion barrier which can lead to a mismatch between oxygen supply and demand. The consequences of such oxygen limitation are hatching delays (Fernández et al 2003 ) and subsequent catch-up growth even when favourable conditions for larval life are reinstated (Petersen and Anger 1997 ; Warkentin 2002 ; Horváthová et al 2017 ). Several studies have shown changes in mass exponents through the ontogeny of different taxa which is in agreement with our findings (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the colonization of land by isopods ca. 300 Mya [5,6] coincided with peak levels of atmospheric oxygen, followed by a large (50%) and rapid decrease in the atmospheric oxygen content [6,7]. Therefore, isopod lineages evolving a terrestrial lifestyle experienced dramatic shifts in oxygen availability throughout their evolutionary history: from the relatively low oxygen availability in aquatic environments [8] to the initially high but later decreased oxygen availability on land.…”
Section: Introductionmentioning
confidence: 99%
“…The oostegites of females, which are specialized limbs, enlarge to form the brood pouch in the anterior ventral side of the body, covering the oviducal openings. Montalentl, 1990), and the development of brood pouches (Ridley and Thompson, 1979), have been associated with the evolutionary success of A. aquaticus, and of Isopoda in general (Hornung, 2011;Horváthová et al, 2017). In general, A. aquaticus inhabits a variety of natural (and man-made) aquatic habitats, and is common in lakes, ponds, rivers, and creeks across Europe and parts of Asia.…”
Section: Asellus Aquaticus As a Model System For Integrative Studiesmentioning
confidence: 99%